Health risk assessment of Pb, Cd, and Zn in leafy and bulb vegetables from northern Iran using Monte Carlo simulation - Elham Falahati Naghibi; Seyed Mahmoud Mehdinia; Abdoliman Amouei (Environmental Research Communications, 2025)
Vegetables are important sources of essential minerals and vitamins for a healthy life. However, vegetable contamination may cause severe health risks. The present study evaluated the health risks of three heavy metals (HMs) including lead (Pb), cadmium (Cd), and zinc (Zn) in six types of vegetables commonly consumed in the north of Iran (Dill, Onion, Fenugreek, Garlic, Spinach, and Peppermint). A total of 60 vegetable samples were collected and analyzed using the standard methods. The mean concentrations were 1.55 (Pb), 0.05 (Cd), and 10.43 (Zn) mg/kg dry weight (DW). The results revealed that the concentration of Pb in all vegetables and that of Cd in onions were higher than the World Health Organization (WHO)‘s maximum allowable concentrations. The probabilistic health risk assessment through consumption of the studied vegetables for adults and children was estimated using the Monte Carlo simulation (MCS). The 95th percentile estimated Hazard index (HI) for the six vegetables ranged from 0.02 to 0.53 for adults and 0.03 to 0.87 for children. Correspondingly, the Target carcinogenic risk (TCR) values ranged from 8.21 × 10 ^−7 to 3.67 × 10 ^−5 for adults and from 1.58 × 10 ^−6 to 5.20 × 10 ^−5 for children. Although the MCS indicated that the 95th percentile values of the HI and TCR for any of the six vegetables in both populations exceeded point estimates, they remained below permissible thresholds, (HI < 1, TCR < 1 × 10 ^−4 ). However, the high concentration of metals, especially Pb in these vegetables necessitates special attention in their long-term consumption. To reduce the adverse effects of vegetables contaminated with HMs, it is necessary to use organic fertilizers and reduce the consumption of chemical fertilizers, prohibit the use of sewage sludge, and implement careful and continuous monitoring of soil and irrigation water.